A rational analysis of the benefit of free justice and the setting of parameters for its concession (Research, Society and Development, 2022)
This scientific article aims to elucidate the parameters for setting the benefit of free justice and accountability in cases of improperly granted benefit. To better elucidate the problem, a discussion was made about the historical content of free justice, where the advancement of this institute over the years was observed. Therefore, observing the doctrinal concept of free justice in distinction from free legal assistance. In view of the legal and jurisprudential requirements for its concession and the nuances of this in civil procedural law. Subsequently, it was elucidated about the responsibility applied to cases of misuse of the benefit of gratuitousness of justice. In view of the facts and the importance of the subject, the general objective was to clarify the nuances of the institute of free justice in the Brazilian legal system. The specific objectives are: a) to discuss the historical context of the institute of free justice; b) address free justice in light of the CF/1988 and the CPC; c), provide for the requirements for granting the benefit of free justice in the light of jurisprudence, finally, d) expose the accountability of agents who request free justice in bad faith, through deepening their bibliographic and documentary research. Finally, the exploratory methodology was used, in order to clarify, develop or even modify concepts and ideas, with analysis of documents, interviews, reports of real cases and legal decisions. The method used in the research was the indirect inductive method.